Cytotoxicity and Apoptosis Induction of 6,7-Dehydroroyleanone from Taiwania cryptomerioides Bark Essential Oil in Hepatocellular Carcinoma Cells - Guan-Rong Chen; Mei-Ling Chang; Shang-Tzen Chang; Yu-Tung Ho; Hui-Ting Chang (MDPI AG, 2022)
The objective of the present study is to evaluate the cytotoxicity of Taiwania cryptomerioides essential oil and its phytochemical on the Hep G2 cell line (human hepatocellular carcinoma). Bark essential oil has significant cytotoxicity to Hep G2 cells, and S3 fraction is the most active fraction in cytotoxicity to Hep G2 cells among the six fractions. The diterpenoid quinone, 6,7-dehydroroyleanone, was isolated from the active S3 fraction by bioassay-guided isolation. 6,7-Dehydroroyleanone exhibited significant cytotoxicity in Hep G2 cells, and the efficacy of 6,7-dehydroroyleanone was better than the positive control, etoposide. Apoptosis analysis of Hep G2 cells with different treatments was characterized via flow cytometry to confirm the cell death situation. Etoposide and 6,7-dehydroroyleanone could induce the apoptosis in Hep G2 cells using flow cytometric assay. Results revealed 6,7-dehydroroyleanone from T. cryptomerioides bark essential oil can be a potential phytochemical to develop the anticancer chemotherapeutic agent for the treatment of the human hepatocellular carcinoma.